Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/mats.201600074
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Laws of Bottle‐Brush Polymers in Dilute Solutions

Abstract: The structural determination and manipulation of bottle-brush polymers, a class of polymers with serially grafted side-chains, is challenging due to the interplay of side-chain and backbone interactions over various length scales. The present work performs a detailed analysis, using molecular dynamics simulation techniques, to unravel these interactions by probing the distinct rod to a flexible real-chain with self-avoiding walk (SAW) type crossover in the backbone static structure factor. This analysis elucid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 33 publications
4
24
0
Order By: Relevance
“…The result supported the prediction of the scaling theory only in the case of longer side chains ( N g = 20 ∼ 40, N b = 800, σ –1 = 10), but not in the case of shorter side chains and spacers . In contrast, the molecular dynamics simulation from Chatterjee et al confirmed the validity of predictions by Fredrickson . In addition to the above approaches, alternative approaches have been used to understand the behavior of bottlebrush polymers, including the self-consistent field theory, renormalization group methods, and the Rosenbluth method …”
Section: Theoretical Backgroundmentioning
confidence: 72%
See 1 more Smart Citation
“…The result supported the prediction of the scaling theory only in the case of longer side chains ( N g = 20 ∼ 40, N b = 800, σ –1 = 10), but not in the case of shorter side chains and spacers . In contrast, the molecular dynamics simulation from Chatterjee et al confirmed the validity of predictions by Fredrickson . In addition to the above approaches, alternative approaches have been used to understand the behavior of bottlebrush polymers, including the self-consistent field theory, renormalization group methods, and the Rosenbluth method …”
Section: Theoretical Backgroundmentioning
confidence: 72%
“…18 In contrast, the molecular dynamics simulation from Chatterjee et al confirmed the validity of predictions by Fredrickson. 23 In addition to the above approaches, alternative approaches have been used to understand the behavior of bottlebrush polymers, including the self-consistent field theory, 24 renormalization group methods, 25 and the Rosenbluth method. 26 Quasi-Two-Parameter (QTP) Theory.…”
Section: ■ Theoretical Backgroundmentioning
confidence: 99%
“…24 Some agreement with molecular dynamics simulations have been observed. 59 Alternative approaches have also been used to understand bottlebrush structure, including perturbative methods, 60 self-consistent field theory, 61 and renormalization group methods. 62,63 Indeed, while most recent work has focused on models for dense melts, [64][65][66][67][68][69][70][71] there remains a need for further insight into dilute-solution bottlebrush structure.…”
Section: Introductionmentioning
confidence: 99%
“…31 The large volume of experimental and theoretical work remains rife with conflicting ob-servations. 23,24,[30][31][32]35,[49][50][51][52][53][54]59,61,74,75,85 Many of these issues have been discussed at length in a recent review by Binder et al 86 This is in part due to the idealization required to make progress with theory, which is compounded by the reliance on experimental characterization that does not directly image the bottlebrush chains but instead infers structure from model predictions. Furthermore, efforts to include simulation data have often used similarlyidealized molecular models, that rarely invoke the specific chemistry used in a given bottlebrush in favor of universal statements.…”
Section: Introductionmentioning
confidence: 99%
“…This shows some inconsistency with later simulation and theoretical work, 49-55 however Monte Carlo simulations have placed the backbone size exponent to be in the range of 0.6 -0.7. 52,54,[56][57][58] Alternative scaling arguments by Fredrickson,24 who considered the related case of surfactant-associated polymer chains, predicted the effects of progressively increasing the grafting density f as moving through three regimes; a low grafting density where the bottlebrush appears coil-like (f N 59 Alternative approaches have also been used to understand bottlebrush structure, including perturbative methods, 60 self-consistent field theory, 61 and renormalization group methods. 62,63 Indeed, while most recent work has focused on models for dense melts, [64][65][66][67][68][69][70][71] there remains a need for further insight into dilute-solution bottlebrush structure.…”
Section: Introductionmentioning
confidence: 99%